Studi Evaluasi Program Pembinaan Prestasi Balap Sepeda di Ques Cycling Academy Purwokerto - Khairul Mada Setiadi; Bambang Priyono; Cahyo Yuwono; Fery Darmanto (Universitas Negeri Semarang, 2024)
This research aims to analyze the evaluation of the context, input, process and product ofdeveloping cycling performance at Ques Cycling Academy Purwokerto. Data collection techniquesuse observation, interviews and documentation methods. The data analysis techniques in thisresearch are reduction, data presentation, drawing conclusions. This sampling used purposivesampling. Based on the purposive sampling method, a sample of 10 people was obtained consistingof administrators, coaches and athletes. The evaluation results of the context component 3 subaspects were rated 3 good. In the input component, 4 financial sub-aspects got 1 good and 3 fair, government support was categorized as poor, 3 sub-aspects of parent and community support got 2 good marks and 1 fair score, 2 athlete sub-aspects got 2 good marks, 6 coach sub-aspects got scores 3 is good, and 3 is sufficient, 2 management sub-aspects get a score of 2 good. In the process component, 7 sub-aspects of organizational management got a score of 7 good, 3 sub-aspects of infrastructure got a score of 2 good and 1 fair, 4 sub-aspects of training programs got a score of 4 good, 2 sub-aspects of athlete rights got 1 good score and 2 fair scores, 4 The competition sub-aspect received a score of 4 good, the 3 sub-aspects of applying science and technology received a score of 3 good, the 3 sub-aspects of media support received a score of 1 good, a score of 1 sufficient and a score of 1 poor. In the product component, 3 sub-aspects are rated 3 good